2020
DOI: 10.1182/bloodadvances.2020002252
|View full text |Cite
|
Sign up to set email alerts
|

Complement inhibition does not impair the clinical antiviral capabilities of virus-specific T-cell therapy

Abstract: Key Points The use of terminal complement blockade is compatible with virus-specific T-cell (VST) expansion and clinical effectiveness. VST and complement-blocking agent concurrent therapy may be safely used in patients with thrombotic microangiopathy and viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Crosstalk between complement pathways and adaptive immunity have been described, and C5a has been shown to impact activity of antigen presenting cells as well as survival, differentiation, and activity of CD4 + T cells [68][69][70][71][72] . Of note, Rubinstein et al did not note an adverse impact of TMA or eculizumab treatment on clinical response to VST therapy in 13 patients, and demonstrated persistent interferon-γ release during complement inhibition 73 . Viral load, patient acuity, and degree of HLA match did not appear to impact chances of responses, though confirmation of an HLA restriction shared between the VST donor and recipient trended toward improved responses.…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk between complement pathways and adaptive immunity have been described, and C5a has been shown to impact activity of antigen presenting cells as well as survival, differentiation, and activity of CD4 + T cells [68][69][70][71][72] . Of note, Rubinstein et al did not note an adverse impact of TMA or eculizumab treatment on clinical response to VST therapy in 13 patients, and demonstrated persistent interferon-γ release during complement inhibition 73 . Viral load, patient acuity, and degree of HLA match did not appear to impact chances of responses, though confirmation of an HLA restriction shared between the VST donor and recipient trended toward improved responses.…”
Section: Discussionmentioning
confidence: 99%
“…9 No large study has described the effect of eculizumab on T-cell function during engraftment. However, a prior study by Rubinstein et al 26 showed that eculizumab therapy did not impair viral specific T-cell function in patients who underwent HCT. Furthermore, multiple studies have shown no adverse effect of pre-HCT eculizumab therapy on engraftment in patients with paroxysmal nocturnal hemoglobinuria.…”
Section: Donor Chimerismmentioning
confidence: 93%
“…Virus specific T‐cells (VSTs) are a particularly exciting new era of less toxic anti‐viral therapies, that will hopefully reduce the incidence of viral induced TMAs. We have previously shown that VST efficacy is not impaired by eculizumab, which means the two treatments can be safely used together 80 …”
Section: Additional Considerations For Ta‐tma Therapy and Complement ...mentioning
confidence: 95%
“…C5a or C5aR1 blockade can theoretically inhibit VSTs but this pathway is importantly unaffected by C5 blockers like eculizumab 112–114 . Rubinstein et al also previously showed that VSTs are fully functional with concurrent C5 blockade 80 …”
Section: Additional Considerations For Ta‐tma Therapy and Complement ...mentioning
confidence: 99%